Dynamic Stability of Piezoelectric Plate Reinforced with BNNTs Considering Temperature Effect. (3rd May 2020) - Yang, Jinhua; Sun, Gaofeng; Zhou, Tao; Yang, Jie
Abstract : Subjected to axial dynamic load, the dynamic stability of piezoelectric plate reinforced with boron nitride nanotube (BNNT) is investigated. Recurring to classical thin plate theory and piezoelectric theory containing thermal effects, the constitutive equation of the piezoelectric plate reinforced with BNNTs is set up. Adopting 'XY' rectangle model, the material constants are reckoned. Afterwards the dynamic control equation of the structure is deduced through Lagrangian equation and resolved by using the Bolotin method. In numerical calculations, the influence of temperature, voltage, boundary condition, volume fraction, material property and static loading parameter on the principal instability region of BNNTs reinforced piezoelectric plate are discussed in detail.